Publicznoprawne funkcje kapitana statku morskiego - Zyzda, Barbara (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The article presents public functions of shipmaster. A shipmaster’s responsibilities are wide-ranging in expertise and encompass navigation, business functions, operation of the ship’s equipment, monitoring of duties performed by crew members, keeping regular logs throughout the journey. The author analyzes the legal duties of captain based on local and international laws.
Keywords: kapitanowie statków; funkcje publicznoprawne; statki morskie